Poly(3, 4 ethylenedioxythiophene)‐tosylate—Its synthesis, properties and various applications. (15th December 2020) - Maity, Shilpa; Datta, Salini; Mishra, Megha; Banerjee, Shiladitya; Das, Sukhen; Chatterjee, Krishanu
Abstract: The discovery of conducting polymers (CPs) opens up a new path for the researchers to design them accordingly to some specific applications. Poly(3, 4ethylenedioxythiophene)‐tosylate (PEDOT‐Tos) being one of the bicyclic polythiophene derivatives has been drawing much attention in the recent years. PEDOT is a well‐known CP with high electrical conductivity and balanced with small counter ion Tos seems to be a material capable in various applications. The improved structural order with the semi‐metallic character as supported by the electronic band structure activates the scientific community to employ PEDOT‐Tos in various applications. Reports show that for the last decade categorically PEDOT‐Tos has been synthesized, which finds applications not only in thermoelectrics, different type of sensors including mechanical and optical, as electrodes in organic electronics but also in biomedical applications specifically in tissue culture. The present work aims at implementing a comprehensive update on the synthesis of PEDOT‐Tos with the structure and properties and also a state‐of‐art review as a promising material in various applications with anticipation that the present work motivate the researchers to bring out PEDOT‐Tos as a multifunctional material.